Spletišče Uporabna geografija v novi podobi in z novimi posodobljenimi orodji - Kikec, Tatjana (Geografija v šoli, 2024)
The rapid advancement of information and communication technology has contributed to its broad use and rendered it indispensable in the educational process. The revamped Applied Geography website compiles a collection of online and mobile tools for classroom use that we can apply for lesson design, classwork, fieldwork, school excursions or optional subjects. The tools are particularly well-suited when using smart mobile devices in the field, which increases student motivation. It supports planning school excursions and includes theme-based online and mobile apps that allow user collaboration on map creation for a specific subject. The map search engine enables you to search for selected locations and a wide range of thematic data layers, design a map and use it in the field to gather information about a particular area of interest. The website enables teachers and students to acquire new skills, increase digital literacy and improve their digital competencies. The rapid advancement of information and communication technology has contributed to its broad use and rendered it indispensable in the educational process. The revamped Applied Geography website compiles a collection of online and mobile tools for classroom use that we can apply for lesson design, classwork, fieldwork, school excursions or optional subjects. The tools are particularly well-suited when using smart mobile devices in the field, which increases student motivation. It supports planning school excursions and includes theme-based online and mobile apps that allow user collaboration on map creation for a specific subject. The map search engine enables you to search for selected locations and a wide range of thematic data layers, design a map and use it in the field to gather information about a particular area of interest. The website enables teachers and students to acquire new skills, increase digital literacy and improve their digital competencies.
Keywords: digitalna kartografija; ekskurzije; excursions; Geografija; geography; ICT; IKT; Informacijsko-komunikacijska tehnologija; map search; mobile apps; mobilne aplikacije